SENAM KAKI DIABETIK BERPENGARUH TERHADAP PENINGKATAN ANKLE BRACHIAL INDEX (ABI) PADA PENDERITA DIABETES MELITUS TIPE II - Andri Setyorini; Alifiah Asty Sasbilla (STIKES Pemkab Purworejo, 2023)
Diabetes mellitus is a chronic disease that occurs as a result of pancreatic dysfunction and insufficient insulin production or when the body cannot effectively use insulin, causing hyperglycemia. Diabetes mellitus plays an important role in the occurrence of peripheral vascular disease which is characterized by obstructed blood circulation in the leg area. Peripheral vascular disease can be detected earlier by measuring the ABI value and can be prevented by doing diabetic foot exercises. This study aims to determine the effect of diabetic foot exercise on the value of the ankle brachial index in patients with type 2 diabetes mellitus at the Jetis 2 Health Center. This quantitative study used a pre-experimental design with a one group pre-post test design approach. The population in this study were all type 2 diabetes mellitus patients undergoing treatment at the Jetis II Health Center, patients aged 30-50 years, not having diabetic foot ulcer complications, general condition and vital signs were good, able to mobilize freely and did not suffer from diabetes mellitus. disturbance in sitting. From these results, there were 24 respondents according to DM registration data for 2022 at the Jetis 2 Health Center. The sampling technique used was simple random sampling. Data analysis used the Wilcoxon sign rank test. After conducting bivariate analysis with the Wilcoxon sign rank test, the Z value is -3.542 with Asymp. Sig. (2-tailed) ie 0.000 <0.05 which means that there is a significant effect of diabetic foot exercise on ABI values ​​in patients with type II diabetes mellitus. It is hoped that the results of this study can be used as a source of information and reference material in carrying out alternative interventions, especially for Diabetes Mellitus patients in an effort to improve ankle brachial index (ABI) values ​​in order to minimize vascular complications that are likely to occur